2017
DOI: 10.1186/s12934-017-0764-z
|View full text |Cite
|
Sign up to set email alerts
|

Mixomics analysis of Bacillus subtilis: effect of oxygen availability on riboflavin production

Abstract: Background: Riboflavin, an intermediate of primary metabolism, is one kind of important food additive with high economic value. The microbial cell factory Bacillus subtilis has already been proven to possess significant importance for the food industry and have become one of the most widely used riboflavin-producing strains. In the practical fermentation processes, a sharp decrease in riboflavin production is encountered along with a decrease in the dissolved oxygen (DO) tension. Influence of this oxygen avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…B. subtilis has been widely used to produce amino acids ( 17 ) and vitamins ( 18 ). Since oxygen is required for the production of these compounds ( 19, 20 ), B. subtilis probably produced such reducing agents under oxic conditions, resulting in the lower ORP values observed in this study.…”
Section: Resultsmentioning
confidence: 70%
“…B. subtilis has been widely used to produce amino acids ( 17 ) and vitamins ( 18 ). Since oxygen is required for the production of these compounds ( 19, 20 ), B. subtilis probably produced such reducing agents under oxic conditions, resulting in the lower ORP values observed in this study.…”
Section: Resultsmentioning
confidence: 70%
“…2012) Under oxygen‐limited conditions, the metabolic flux of the PP pathway decreases, and the transcription level of ykgB decreases (Hu et al . 2017). Overexpression of ykgB has a certain effect on the synthesis of the downstream metabolite uridine of PRPP (Zhang and Wang 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that under hypoxic conditions, the metabolic flux of the PP pathway decreases, accompanied by a decrease in ykgB transcription levels (Hu et al . 2017). In B. subtilis , there is a balanced relationship between de novo IMP and the UMP synthesis pathway (Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…The increase in growth yield due to surfactin suggests that oxygen can be limiting even in aerobic cultures and that increasing oxygen availability increases yield. This finding has industrial implications as B. subtilis is commonly used to produce many enzymes and antibiotics [53], and maintaining oxygen levels is critical to optimize production of the desired compounds [54,55]. In addition to oxygen, surfactin might also facilitate growth by increasing nutrient diffusion during late exponential phase when nutrients become limiting.…”
Section: Discussionmentioning
confidence: 99%